Rural Education and Special Education: the dialogue of inclusive modalities in contemporary times - Taiana Furtado dos Anjos; Allan Rocha Damasceno (Universidade Federal do Norte do Tocantins, 2020)
This article discusses the theoretical and conceptual reflections of the interface between Special Education and Rural Education in the context of Brazilian public policies in contemporary times. Therefore, it is necessary to understand the concept of Rural Education within a historical approach drawn by social movements against the mechanisms of exclusion and segregation of peasant subjects, including in this process the target audience of Special Education, strengthening the movement of struggle and resistance to guarantee inclusive social rights already won in the legal provisions. Our intention is to present the main legal frameworks of Brazilian educational legislation, seeking to identify the elements that establish a dialogue between Special Education and Rural Education as modalities of Inclusive Education in contemporary society, with emphasis on the Operational Guidelines for Basic Education in Rural Schools and its Complementary Guidelines and the National Policy on Special Education from the perspective of Inclusive Education, among others. This article is a bibliographic essay that uses the lens of Critical Theory, with emphasis on Theodor Adorno's thinking, in the critical-reflexive analysis of Special Education in the Field, resulting in the identification of the main elements of convergence that consolidate the interface between the modalities aforementioned, evidencing the necessary articulation in the consolidation of inclusive public policies for students targeting Special Education in rural schools.